PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT BORNEO INDAH DI SAMARINDA - Robi Hidayat; Djoko Setyadi; Ariesta Heksarini (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study determine the influence of motivation and work environment to the Employee Performance PT Borneo Indah In Samarinda and determine the influence of these two variables motivation and work environment, where the dominant influence on employee performance PT Borneo Indah in Samarinda. Basic theory used human resource management by using multiple linear regression analysis with 41 samples.Conclusions of the study:Motivation and Environment together with significant influence on employee performance in PT Borneo Indah In Samarinda, said the research hypothesis is acceptedMotivation dominant influence on employee performance in PT Borneo Indah In Samarinda, said the research hypothesis is accepted Keywords: Motivation, Work Environment - Performance